Hand Parameters and Walking Stick Design: A Case Study among Elderly Malaysian - Saptari, A.; Halim, I.; Mohamed, M.S.S.; Fauzi, A.M. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
According to the World Bank, in 2015, the elderly population reaches 8.5% of the world's population. This number grows at 0.13% per annum. In Malaysia, the growth reaches 0.2% of this population annually. Assistive tools such as a walking stick to support the elderly people have become necessary. However, much uncertainty still exists about the relation between the walking stick design and the Malaysian elderly. The objectives of the study were to measure hand dimension and hand grip strength of Malaysian elderly and to relate the hand dimension with the walking sticks being used. There were 50 Malaysian elderly participated in this study and three designs of walking stick available in the market were tested. The first design (handle A) was round and padded, the second design (handle B) was rectangular curve and the third design (Handle C) was round curve. Statistical analysis between hand size and hand surface area shows a linear relationship with R2 = 54% and significant with p-value < 0.05. As for the relationship between the contact area of stick handle and hand size, a linear relationship was found with R2 = 53.3% for handle A, R2 = 46.5% for handle B, and R2 = 36.6% for handle C. This study concluded that the walking stick with high contact area provides better grip and comfort.